Abdominal obesity and risk of CVD: a dose–response meta-analysis of thirty-one prospective studies. Issue 9 (14th November 2021) - Xue, Ran; Li, Qianwen; Geng, Yaping; Wang, Hao; Wang, Fudi; Zhang, Shenshen
Abstract: This meta-analysis aimed to study the relationship between abdominal obesity and the risk of CVD by waist circumference (WC), waist:hip ratio (WHR) and waist:height ratio (WHtR). We systematically searched PubMed, Embase and Web of Science. Prospective studies that estimated cardiovascular events by WC, WHR and WHtR were included in this study. Pooled relative risks with 95 % CI were calculated using random effects models. A total of thirty-one studies were included in the meta-analysis, including 669 560 participants and 25 214 cases. Compared the highest with the lowest category of WC, WHR and WHtR, the summary risk ratios were 1·43 (95 % CI, 1·30, 1·56, P < 0·001), 1·43 (95 % CI, 1·33, 1·54, P < 0·001) and 1·57 (95 % CI, 1·37, 1·79, P < 0·001), respectively. The linear dose–response analysis revealed that the risk of CVD increased by 3·4 % for each 10 cm increase of WC, and by 3·5 and 6·0 % for each 0·1 unit increase of WHR and WHtR in women, respectively. In men, the risk of CVD increased by 4·0 % for each 10 cm increase of WC, and by 4·0 and 8·6 % for each 0·1 unit increase of WHR and WHtR, respectively. Collectively, abdominal obesity is associated with an increased risk of CVD. WC, WHR and WHtR are good indicators for the prediction of CVD.